Chicken Nugget in scrambled egg - Robinson, Michelle 1977- (Puffin, 2017)
My name is Nugget. Chicken Nugget ...It's not easy being the smallest chick in the family, but Nugget has had some good news: he's going to be a big brother! Little baby Benedict is still an egg at the moment and it's Nugget's job to look after him. What could possibly go wrong? Another cracking story from bestselling duo Michelle Robinson and Tom McLaughlin
Keywords: Eggs / Juvenile fiction; Chickens / Juvenile fiction; Courage / Juvenile fiction; Brothers and sisters / Juvenile fiction; Children's stories; Brothers and sisters; Chickens; Courage; Eggs; Fiction; Juvenile works; Children's picture books; Children's stories / Pictorial works; Bilderbuch